PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. BUMI SARIMAS INDONESIA - , Marina, Prof. M. Hawin, S.H., LL.M, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Corporate Social Responsibility (CSR) is a discourse that was prominent in the corporate world. Provisions on CSR in Indonesia regulated in Capital Investment Law Number 25/2007 and Limited Company Law Number 40/2007. Article 74 of Limited Company Law said the company with business in the field and / or relating to natural resources required to implement the Social and Environmental Responsibility. One company that runs its business activities in the field of natural resources is PT. Bumi Sarimas Indonesia (PT. BSI). Aim in this study is how the implementation of CSR in the PT. BSI and what are the detention of PT. BSI in implementing CSR. The method used is the Juridical Sociological, which approaches the problem through legislation and existing theories and then connects it to the facts on practice, with the descriptive research, to obtain a complete and thorough overview on the implementation of CSR in the PT. BSI. The results showed that the implementation of CSR in the PT. BSI is not in accordance with the provisions of Article 74 paragraph (1) Limited Company Law, because concept of CSR by PT. BSI are voluntary activities, rather than something that is mandatory (liabilities). Source of fund the implementation of CSR by PT. BSI came from the company profit and partially budgeted each month, is also not fully in accordance with the provisions of Article 74 paragraph (2) Limited Company Law. Detention of PT. BSI in implementing CSR is a lack of socialization of this Limited Company Law by the government, less of the assistance provided to the community due to many other corporate expenses that are not mandatory, and providing assistance to the area around the company made an envy of other areas that do not receive assistance from the company. In order to better implementation of CSR, the government should continue to socialization Limited Company Law to the businessman to get an equate perceptions of CSR, companies should regularly to make the implementation of CSR each year, it takes consistency and commitment from governments and companies in implementing CSR, and the government is expected to issue regulations of the CSR, to make clear and unequivocal concept about CSR.